2016
DOI: 10.3762/bjoc.12.286
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of nanosized titanium dioxide by cyclodextrin polymers and its photocatalytic effect on the degradation of wastewater pollutants

Abstract: Advanced oxidation processes (AOPs) are considered highly competitive water treatment technologies for the removal of organic pollutants. Among AOP techniques, photocatalysis has recently been the most widely studied. Our aims were to investigate how the dispersion of nanosized titanium dioxide (nanoTiO2) applied in photodegradation-based procedures can be stabilized with cyclodextrins in order to obtain a new, more efficient photocatalyst for the purification of waters polluted by xenobiotics applying UV irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 40 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the presence of βCD seems to have a slightly protective effect on the polymers in comparison with the unmodi ed NPs. Previous studies have reported a stabilizing effect of the CDs on TiO 2 NPs [49], and this could improve its integration with the polymeric matrices. Comparing both biopolymers, PLA samples underwent greater damage in shorter times than CA.…”
Section: Thermogravimetric Analysismentioning
confidence: 95%
“…Moreover, the presence of βCD seems to have a slightly protective effect on the polymers in comparison with the unmodi ed NPs. Previous studies have reported a stabilizing effect of the CDs on TiO 2 NPs [49], and this could improve its integration with the polymeric matrices. Comparing both biopolymers, PLA samples underwent greater damage in shorter times than CA.…”
Section: Thermogravimetric Analysismentioning
confidence: 95%
“…Agócs et al [232] obtained 81% degradation of IBP (50 µM) in pure water after 60 min of treatment in the presence of nanometric TiO 2 , stabilized with cyclodextrins, under UV irradiation. In tap water, the degradation was slower due to loss of efficiency of the oxidizing agents.…”
Section: Ibuprofenmentioning
confidence: 99%